PENETAPAN ESTIMASI HARGA JASA TITIP BARANG LUAR NEGERI DITINJAU DARI PRINSIP EKONOMI ISLAM - Nurhidayah, Nurhidayah; Wahyuni, Wahyuni; Otong Karyono, (Nusantara Hasana Journal, 2024)
This research aims to analyze the determination of price estimates for foreign goods delivery services from an Islamic economic perspective. Overseas goods delivery services are a solution for consumers who want to get products from abroad easily and quickly without going through a complicated purchasing and shipping process. This research identifies the factors that influence price setting, examines the extent to which current pricing practices are in accordance with Islamic economic principles, and provides recommendations for service providers to be able to set fair and transparent prices in accordance with Islamic economic values. The research method used is a qualitative analysis technique with primary data in the form of open interviews with jastip business people and secondary data from related literature. The research results show that the principles of justice, balance and transparency in Islamic economics are very important in determining prices for entrusted services. Pricing that is carried out transparently and honestly can be accepted by consumers, thereby ensuring fair and profitable transactions for both parties.